A demonstration concentrating solar power plant in China: Carbon neutrality, energy renewability and policy perspectives. (15th February 2023) - Ye, Huafeng; Peng, Huaiwu; Li, Chaohui; Li, Yilin; Li, Zhi; Yang, Qing; Chen, Guoqian
Abstract: Concentrating solar power (CSP) is considered as a promising renewable electricity source due to its superiority in providing dispatchable and base-load electricity. This study performs a systems process analysis to quantify the carbon emissions and nonrenewable energy costs induced by a state-of-art demonstration CSP plant located in the Tibetan plateau. Estimated to induce 111.2 g CO2 eq/kWh carbon emissions and 1.42 MJ/kWh non-renewable energy consumption, the CSP plant is considered to have extremely high carbon neutrality (88.8%) and energy renewability (86.4%). The prominent performance of carbon emissions reduction and energy conservation induced by the CSP plant shed light on its superiority of reliable power supply and environmental benefits. The plant is expected to cumulatively fulfill 3.4 million tons of carbon emissions reduction over its life cycle. In contrast to coal-based power and other renewable energy technologies, CSP technology is shown to be a promising solution to the low-carbon energy transition. Besides, a scenario analysis indicates that the incremental employment of CSP technologies will play a critical role in coping with climate change and energy security in China. Moreover, multiple policies to facilitate the development of the CSP system in China are elaborated, such as the promotion of integrated solar combined-cycle systems. The empirical finding draws a holistic picture of the carbon neutrality and energy sustainability performance of CSP technologies, and the systematic analysis in this study provides comprehensive policy perspectives for energy policy in the Tibetan region as well as in China in the context of global climate change. Highlights: ·The CSP plant is characterized by extremely high carbon neutrality (88.8%). The CSP plant is characterized by extremely high energy renewability (86.4%). The CSP plant can reach 3.4 Mt of CO2 reduction during its life cycle. CSP technology is a promising solution to China's carbon neutrality goal.